Immunotherapy in Adolescents and Young Adults: What Remains in Cancer Survivors? - Tanda, Enrica Teresa; Croce, Elena; Spagnolo, Francesco; Zullo, Lodovica; Spinaci, Stefano; Genova, Carlo; Rossi, Giovanni (Frontiers in Oncology, 2021)
Immunotherapy has changed the landscape of treatments for advanced disease in multiple neoplasia. More and more patients are already considered long survivors from a metastatic disease. Most recently, the extension of indications and evidence of efficacy in early disease settings, such as the adjuvant and neoadjuvant setting in breast cancer, lung cancer, gliomas and gastric cancer places more attention on what happens to patients who survive cancer. In particular, we have evaluated what happens in younger patients in whom some effects are currently little or not at all studied. Immunotherapy is already a reality in early disease settings and the scientific community is lagging in describing what to expect in these patients. In particular, to date, the impact that these therapies have on female and male fertility is not clear, just as it is not clear that interactions can exist between these drugs and pregnancy. This review aims to highlight these little-known topic that are difficult to study in trials studied ad hoc.